The space dimension of alternative history: Popular science, transmedia storytelling, and the contemporary agenda - E. G. Lapina-Kratasyuk (Шаги, 2022)
The purpose of the article is to consider the possibilities that the genre of alternative history applied to the history of space, scientific and technical achievements of the 20th century opens to public history and popular science professionals. The genre of alternative history, firstly, allows us to draw public attention to the fact that global scientific discoveries and technological inventions are no less important facts of modern history than wars and political confrontations. Secondly, due to stories that are deliberately antonymous to “textbook history” (for example, “Alexey Leonov landed on the Moon first”), an alternative history provokes viewers to consider in detail the documentable past. And finally, with the help of transmedia storytelling and modern digital tools, the historical project can be extended to topics from the natural and engineering sciences (for example, by studying a 3D virtual model of the lunar station). In addition, transmedia storytelling involves expanding an audience’s experience: now its members can not only watch a serialized program, but also be involved in gaming and crowdsourcing practices in the project’s applications. In general, this approach draws attention to the multivariance of the past, and to the uncertainty of events and ideological schemes of the history of the Cold War and the first space race.